Epidemiology of HIV among black and minority ethnic men who have sex with men in England and Wales. Issue 4 (1st August 2005) - Dougan, S; Elford, J; Rice, B; Brown, A E; Sinka, K; Evans, B G; Gill, O N; Fenton, K A
Abstract : Objectives: To examine the epidemiology of HIV among black and minority ethnic (BME) men who have sex with men (MSM) in England and Wales (E&W). Methods: Ethnicity data from two national HIV/AIDS surveillance systems were reviewed (1997–2002 inclusive), providing information on new HIV diagnoses and those accessing NHS HIV treatment and care services. In addition, undiagnosed HIV prevalence among MSM attending 14 genitourinary medicine (GUM) clinics participating in the Unlinked Anonymous Prevalence Monitoring Programme and having routine syphilis serology was examined by world region of birth. Results: Between 1997 and 2002, 1040 BME MSM were newly diagnosed with HIV in E&W, representing 12% of all new diagnoses reported among MSM. Of the 1040 BME MSM, 27% were black Caribbean, 12% black African, 10% black other, 8% Indian/Pakistani/Bangladeshi, and 44% other/mixed. Where reported (n = 395), 58% of BME MSM were probably infected in the United Kingdom. An estimated 7.4% (approximate 95% CI: 4.4% to 12.5%) of BME MSM aged 16–44 in E&W were living with diagnosed HIV in 2002 compared with 3.2% (approximate 95% CI: 2.6% to 3.9%) of white MSM (p<0.001). Of Caribbean born MSM attending GUM clinics between 1997 and 2002, the proportion with undiagnosed HIV infection was 15.8% (95% CI: 11.7% to 20.8%), while among MSM born in other regions it remained below 6.0%. Conclusions: Between 1997–2002, BME MSM accounted for just over one in 10 new HIV diagnoses among MSM in E&W; more than half probably acquired their infection in the United Kingdom. In 2002, the proportion of BME MSM living with diagnosed HIV in E&W was significantly higher than white MSM. Undiagnosed HIV prevalence in Caribbean born MSM was high. These data confirm the need to remain alert to the sexual health needs and evolving epidemiology of HIV among BME MSM in E&W.